Pengenalan Kosa Kata Bahasa Inggris Anak Sekolah Dasar dengan Alphabet and Numberik Method - Ina Magdalena; Asih Rosnaningsih; Hanif Abdul Jabbar (Publikasi Indonesia, 2023)
This study provides a psycholinguistic description of the early infancy process of learning English. The goal of this investigation is to define and clarify how the English learning system functions for kids between the ages of 9 and 10. This study used a descriptive qualitative methodology, and the information came from the sample's feedback after being provided basic language as well as direct interviews with them. The following are the findings of this study: When learning English in early childhood, the child's age can have an impact on how quickly language is absorbed because young children's brains are still developing and are better at remembering small details. Kids are better at remembering new terminology.